Model Pembelajaran Qur’any (Studi Kasus di Yayasan Pendidikan Nasional Ikatan Pendidik IMTAQ Surabaya) - Jamila, Siti Hesniyatul (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This study describes: 1. Implementation Qur-any learning model, The method of model Qur-any, material Qur-any learning model, evaluation Qur-any learning model, excellence Qur-any learning model, and weakness Qur- any learning model in the national education foundation (IMTAQ educator bound) Surabaya. Implementation of Qur-any learning called Active Learning Understood. However, Learning Qur-any superior due also to approach culture through song Qur-any and tikror and drill method. Method: Integrated method drill, tikror, discussion, question and answer, simulations and recitation. Evaluation: Write without copying, the practice of teaching/training and memorized. Material: Qur-any 1, 2, 3, 4, 5, A, B. 6a, 6b, 6c, 6d. Tafsir Amaly. Excellence: Fast, easy, fun, varied, students managed, provided a medium of learning, flexible and inexpensive, regeneration, in accordance with the rules of learning in the Quran, and complete. Weakness: If not paying attention to the principle and guidelines for implementing the learning model Qur-any. Suggestion: Qur-any system that is under the auspices of the national education foundation (IMTAQ educator bound) SK MENKUMHAM: AHU-06844.50.10.2014 Jln. Gayung Kebonsari XV/1, For a while it has a lot of positive values. Therefore, it is worthy of consideration to be implemented throught national and eveninternational policies in all educational institutions.